Predictive modelling of Namibian fairy circles and their co-occurrence with Euphorbia species using Geographical Information Systems (GIS) - Breetzke, Gregory Dennis (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.